Engaging local communities in social learning for inclusive management of native fruit trees in the Central Western Ghats, India - Hegde, N.; Elias, Marlène; Lamers, Hugo A.H.; Hegde, M. (Informa UK Limited, 2017)
Participatory research and the social learning it supports are increasingly being used to improve forest management. Yet, the participation of women and other marginalized groups is often limited in these processes. This is a serious shortcoming, not only due to concerns for gender and social equity, but also because socially excluded, forest-dependent groups hold specific ecological knowledge, skills and interests that influence prospects for sustainable forest management. Carried out in India’s Central Western Ghats, this study explores the potential participatory research holds for engaging communities in a socially inclusive learning process that can support forest management. Participatory tools – resource mapping, Four Cell Analysis, seasonal fruit calendar, and seasonal activity – were used to elicit information on native fruit tree diversity, phenology, agronomy, uses and marketing. We discuss the benefits of this research set-up which promoted interactions among individuals from different groups, who came to experience a common group identity. The notion of contact zones – where different cultures or groups meet and engage with each other in ways that can reduce conflicts or redress asymmetrical power relations – guides our analysis. We demonstrate that the contact zone created through research process facilitated multi-directional information sharing and supported collective actions for forest management.